Fabrication of thermoelectric materials – thermal stability and repeatability of achieved efficiencies. Issue 40 (3rd September 2015) - Aminorroaya Yamini, S.; Brewis, M.; Byrnes, J.; Santos, R.; Manettas, A.; Pei, Y. Z.
Abstract : Thermoelectric properties of metastable metal chalcogenides degrade with thermal cycling. Abstract : Metal chalcogenides have delivered the highest efficiencies among thermoelectric materials. Although the thermal stability of thermoelectric materials at device operating temperatures has been of concern, recent studies have reported the efficiencies of materials prepared with different fabrication techniques. Here, we have fabricated a p-type, multiphase lead chalcogenide compound of (PbTe)0.55 (PbS)0.35 (PbSe)0.1, with three common fabrication techniques of quenched, quenched–annealed and furnace cooled followed by spark plasma sintering. The compound contains PbS-rich precipitates within a PbTe-rich matrix. The achieved samples from various fabrication procedures demonstrate distinct microstructures that evolve with thermal cycling. We have shown that the thermoelectric efficiency of metastable compound is irreversible during thermal cycling, and changes by only three thermal cycles during measurements. Our findings highlight the importance of the choice of fabrication and post-processing techniques for thermoelectric materials.